Labour supply incentives, and income support systems in Estonia - Andres V\~ork (Institute for Labour Market Policy Evaluation (IFAU), 2009)
In this paper we give an overview of labour supply incentives present in the Estonian income support system and how changes during the last ten years in the Estonian benefit system have influenced the incentives. As Estonia belongs to the group of EU countries where both taxes and social expenditures are relatively low, they generate high motivation to actively participate in the labour market, in general. Also the gradual introduction of contribution based and earnings related benefits, such as unemployment insurance benefits, parental benefits, a fully funded pension scheme together with earnings-related public pension scheme have all significantly increased rewards from employment and are often associated with increased labour supply as well as a reduction in undeclared work. The increase of the statutory retirement ages for men and women have increased average employment rates of the elderly, but also retirement through alternative schemes, most notably disability pensions and early retirement pensions. In a few cases, the Estonian benefit schemes generate disincentives to seek for a job or increase labour effort, affecting people both with low and high earnings. In case of unemployment benefits and early retirement benefits, even marginal income from labour leads to loss of all benefits, thus discouraging part time work. Also there are very high effective marginal tax rates when increasing work effort when receiving subsistence benefits and parental benefits, in certain cases. These disincentives become even more significant in this economic crisis when people are faced with long-term unemployment and it is vital that they are encouraged to return to the labour market.
Keywords: H53; H55; J08; J21; J26; 330; Labour supply incentives; social security; Estonia; Arbeitsmarktpolitik; Soziale Sicherung; Alterssicherung; Arbeitslosenversicherung; Arbeitsangebot; Estland